Community characteristics and functional gene response analysis of phosphorus-metabolizing bacteria in plateau saline lake sediments - Yang, Wenhuan; Ma, Jie; Zhen, Yu; Li, Weiping; Yao, Zhi; Feng, Weiying (Frontiers in Environmental Science, 2022)
Microbial phosphorus metabolism in sediments and the biogeochemical cycling of phosphorus have been central issues in lake ecosystems, but the analysis of microbial community characteristics and influential factors of phosphorus metabolic processes in sediments from highland saline lakes have not been well documented. In this study, metagenome sequencing technology was used to analyze the diversity of community characteristics and the relationship between nitrogen and phosphorus functional genes of microorganisms involved in phosphorus metabolic processes in Daihai sediments under high saline conditions, as well as the response of microorganisms involved in phosphorus metabolic processes to changes in environmental factors, including salinity, pH, and the N/P ratio. The results showed that (1) salinity had a positive correlation with the dominant bacteria involved in the major metabolic pathways (ko00030, ko00562, and ko00190) and a negative correlation with those involved in the minor pathways (ko00564 and ko00440); (2) norB and nirS denitrification genes were involved in a major component of phosphorus metabolism, and these functional genes had significant (p < 0.05) effects on phytate hydrolysis, phosphate hydrolysis, and polyphosphate synthesis and decomposition; and (3) environmental factors influenced the diversity of the bacterial community characteristics in the order of salinity > N/P ratio > pH. This study provides new insights into the analysis of the causes of eutrophication and the current state of imbalance in the hydroecological structure of saline lakes on plateaus, as well as an indication of the interactions between the global lake nitrogen and phosphorus cycles.